The Ideals of Body Image through Optical Illusion Pattern: for Less Volume Effect - Rina Watye (Jurnal Ilmiah Publipreneur, 2017)
A person’s satisfaction with the physical image he or she presents to the others is affected by how closely that image corresponds to the image valued by his or her culture on their time live. An ideal of beauty is a particular model, or exemplar, of appearance. Ideals beauty for women may include physical appearance as well as clothing styles, cosmetics, hairstyles, skin tone, and body type. Dresses with optical Illusion to make less volume effect in fashion can be one option for women to make body image more ideals. Optical illusion less volume use human perception, because of our ability to visually assess volumes is not good as our ability to assess areas, fashion with less volume effect have big chance to improve.